On the Diophantine Equation Ln−Lm=11·2^a (European Journal of Pure and Applied Mathematics, 2026)
Using Baker’s method, we completely solve the title equation in positive integers n, m and a for Ln the nth Lucas number.
Keywords: Diophantine equation; Lucas number; Baker’s method